INDIAN INFLUENCE ON JUNGIAN IDEOLOGY - Dr. Shreeja Tripathi Sharma (International Journal of Innovations in Engineering Research and Technology, 2023)
This research paper seeks to explore Carl G Jung’s association with India with the aim of determining the impact of Indian philosophy on Jungian ideology.